Psychological factors and biochemical indicators influencing sleep disturbance of patients with primary biliary cholangitis in China: a cross-sectional survey analysis - Zhao, Chenyang; Zang, Bo; Liu, Qixuan; Liu, Bingqian; Yao, Yuan; Li, Hua; Yang, Yifei; Liu, Bin (Frontiers in Medicine, 2024)
Objective The impact of primary biliary cholangitis (PBC) on sleep disturbance is relevant to treatment decision-making processes. Studies on sleep disturbance in Chinese patients with PBC are still lacking. Methods We analyzed and compared the health-related quality of life (HRQoL) of 107 PBC patients by using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, Generalized Anxiety Disorder Scale (GAD-7), Patient Health Questionnaire 9 (PHQ-9), Short Form (36) Health Survey Questionnaire (SF-36), Fatigue Visual Analog Scale (F-VAS). Patients’ biochemical markers were also collected for correlation analysis with HRQoL. Receiver operating characteristic (ROC) curves and area under the curve (AUCs) were used to determine the diagnostic performance of PSQI, GAD-7, and biochemical markers for assessing the impaired liver function (Child–Pugh B–C) of PBC diagnosis. Results Sixty-two (57.9%) PBC patients suffered from poor sleep quality (PSQI >5). The global PSQI score was positively correlated with GAD-7 (r = 0.561, p < 0.001), and PHQ-9 scores (r = 0.652, p < 0.001). There was a negative correlation (r = −0.216, p = 0.025) between sleep quality and red blood cell (RBC) count. PBC patients with poor sleep quality had significantly higher GAD-7 scores (5 vs. 0, p < 0.001), PHQ-9 scores (5.5 vs. 0, p < 0.001), and lower albumin levels (39.6 vs. 37.6 g/L, p = 0.040) than those with good sleep quality. Based on the SF-36 scores, PBC patients with poor sleep quality had lower physical functioning scores (85 vs. 80, p = 0.022), role physical scores (100 vs. 75, p = 0.007), and worse mental health (60 vs. 56, p = 0.002) than those with good sleep quality. ROC analyses showed that the AUC and optimal cut-off values of the combination of PSQI, GAD-7, and RBC for assessing the impaired liver function in PBC diagnosis were 0.771 and 0.193, respectively. Conclusion The sleep disturbance was strongly correlated with the severity of anxiety, depression, and RBC count in PBC patients. Meanwhile, PBC patients with poor sleep had poor HRQoL and lower albumin levels. It is feasible to use the combination of PSQI, GAD-7, and RBC for initial screening of the impaired liver function in PBC. Besides routine blood biochemical and imaging indicators, evaluating mental health-related indicators in PBC patients is imperative.